The Cybersex Trafficking: Legal Protection Against Child Sexual Exploitation Through Digital Platforms - Ananda Eka Aprilia; Luthfillah Arrizqi Zainsyah (Veteran Law Review, 2025)
The development of digital technology has both positive and negative impacts on society. One negative impact that has emerged is cybersex trafficking, which is a form of child sexual exploitation that uses the internet and digital platforms for human trafficking. This study aims to analyze positive legal regulations in Indonesia regarding cybersex trafficking crimes and the forms of legal protection for children as victims. The method used is normative juridical with a legislative, conceptual, case, and comparative law approach. The results of this study show that Indonesia does not yet have specific regulations governing cybersex trafficking, so it enforces several laws, such as the TPPO Law, the ITE Law, and the TPKS Law. Meanwhile, the Philippines has comprehensively regulated this issue through the OSAEC Act and the Expanded Anti-Trafficking in Persons Act. This situation calls for the establishment of specific regulations in Indonesia to provide effective, comprehensive, and equitable legal protection for children who are victims of sexual exploitation in the digital space.